THE PROTECTIVE EFFECT OF MORINGA TEA AGAINST CYPERMETHRIN-INDUCED HEPATORENAL DYSFUNCTION, OXIDATIVE STRESS, AND HISTOPATHOLOGICAL ALTERATIONS IN FEMALE RATS - Mansour, Sameeh A; Mohamed, Reham I; Ali, Amina R; Farrag, Abdel-razik H (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Exposure to Î±-cypermethrin (Î±-CP) may yield reactive oxygen species (ROS) that is responsible for oxidative stress in mammals. A variety of antioxidants were used to alleviate Î±-CP-induced toxicity in experimental animals. To the best of our knowledge, there are no attempts of using Moringa oleifera L. (MO) plant extracts against Î±-CP-induced toxicity. Therefore, this study was conducted. Methods: A total of 16 adult female rats were segregated into equally four groups: One group administered Î±-CP orally at a dose of 0.05/mg kg bw/ day; and the second group was freely allowed to drink MO leaf extract (moringa tea [MOT]) + the Î±-CP dose. The other two groups represented negative and positive controls. The daily consumption of the solutions was estimated. At the end of experiments (28 day), all animals were subjected to the planned manifestations. Results: MOT has proved its palatability as drinking solution more than water. Compared with control results, the relative weights of liver and brain recorded significant increases, while that of kidney, heart, spleen, ovary, and lung decreased significantly. Furthermore, alterations in the architecture of the liver, kidney, and brain were observed. Î±-CP treatment induced high elevation of the levels of aspartate aminotransferase, alanine amino transferase, alkaline phosphatase, creatinine, and malondialdehyde, while caused decline of butyrylcholinesterase, urea, superoxide dismutase, and total antioxidant capacity levels. Coadministration of MOT restored biochemical and histopathological alterations caused by Î±-CP to a great extent. Conclusion: The present study introduces novel data on the protective effect of MO leaf extract against CP toxicity and sheds light on the palatability of MOTâ€ to rodents.